Differences in Academic Procrastination Attitude Between Fifth Grade Male and Female Students - I Wayan Aan Parantika; Ni Wayan Suniasih; M.G.Rini Kristiantari (Universitas Pendidikan Ganesha, 2020)
Postponing to complete students' academic assignments is known as academic procrastination. This study aims to determine the significant differences in attitudes of academic procrastination between male and female students of fifth grade in Kompyang Sujana Cluster of Elementary School in North of Denpasar, in Academic Year of 2019/2020. This is a comparative ex-post facto causal study. The population of this study were all male and female students of Kompyang Sujana Cluster of Elementary School in Academic Year 2019/2020, with the total of 340 people consisting of 185 male students and 155 female students. The sample was taken from the population using a proportional random sampling technique with total of 172 people (86 male students and 86 female students). The data collected in this study were quantitative attitude of academic procrastination. The data were collected by using the non-test method in the form of a closed questionnaire. Academic attitudes of procrastination data were analyzed using statistical analysis methods namely inferential statistical analysis techniques t-test with separated formulas. Before conducting the data analysis, the analysis prerequisites were tested in the form of a data distribution normality test using chi squared (x2) and homogeneity variance tests using the fisher test. The results of the analysis of procrastination attitude data obtained that tcount = 6.628 > ttable = 1.974 at a significance level of 5% with degrees of freedom (dk) = 86 + 86-2 = 170, then the results of data analysis showed that there were significant differences. Thus it can be concluded that there is significant difference between male and female students' academic procrastination in Kompyang Sujana Cluster of Elementary School in North of Denpasar, in academic year of 2019/2020.